Incidence, Risk Factors, and Prognosis of Hidradenitis Suppurativa Across the Globe: Insights from the Literature - Alotaibi HM (Dove Medical Press, 2023)
Hend M Alotaibi Dermatology Department, College of Medicine, King Saud University, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Hend M Alotaibi, Dermatology department, College of medicine, King Saud University, Riyadh, Kingdom of Saudi Arabia, Tel +966118266482, Email halotaibi1@ksu.edu.saAbstract: Hidradenitis suppurativa, a chronic inflammatory disease of the skin, affects a patient's quality of life to a greater extent. While the disease burden, including its incidence and prevalence, has been extensively studied in the western population, there is a paucity of data from developing countries on the epidemiology of Hidradenitis suppurativa. Therefore, a general literature review was conducted to shed light on the epidemiology of Hidradenitis suppurativa across the globe. We reviewed the most recently available information on epidemiology, including incidence, prevalence, risk factors, prognosis and quality of life, complications, and associated comorbid among patients with Hidradenitis suppurativa. The estimated global prevalence of Hidradenitis suppurativa is found to be 0.00033- 4.1%, with a relatively higher prevalence of 0.7- 1.2% in European and US populations. Both genetic and environmental factors are associated with Hidradenitis suppurativa. Patients with Hidradenitis suppurativa have associated comorbid such as cardiovascular disease, type II diabetes mellitus, mental health issues, and sleep and sexual dysfunctions. These patients spend poor quality of life and tend to be less productive. Future studies are needed to assess the burden of Hidradenitis suppurativa in developing countries. Since the disease tends to be underdiagnosed, future studies should rely on clinical diagnosis rather than self-reporting to avoid the potential of recall bias. Attention needs to be diverted to developing countries with less amount of data on Hidradenitis suppurativa.Keywords: Hidradenitis suppurativa, epidemiology, globe, literature review